(untitled) (Revista Internacional de Formação de Professores, 2022)
The objective of this study was to investigate existing relationships between CAPES Notices 06/2018 and 01/2020 on Pedagogical Residency, making considerations about the points and counterpoints in these documents. A qualitative analysis was performed and the instruments for obtaining information were the aforementioned notices. It was found that the program has obstacles since its genesis, being extended to the present day, it is also observed that there are advances and setbacks present in the 2020 public notice. It is necessary that echo voices advocating for the continuity of the program and that they mobilize themselves producing investigations that point out the relevance and reveal the adversities of the program